2021
DOI: 10.1051/epjconf/202124716006
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Modeling Approach to Estimate Radiation From a Spent Fuel Rod Quiver

Abstract: Before encapsulation of spent nuclear fuel in a geological repository, the fuels need to be verified for safeguards purposes. This requirement applies to all spent fuel assemblies, including those with properties or designs that are especially challenging to verify. One such example are quivers, a new type of containers used to hold damaged spent fuel rods. After placing damaged rods inside the quivers, they are sealed with a thick lid and the water is removed. The lid is thick enough to significantly reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 3 publications
4
3
0
Order By: Relevance
“…The serpentTools [28] package was used to read in the detector tallies in the output files from the particle transport calculations carried out in Serpent2 to create the plots shown in figure 8. The results from the first part of this study were found to be in line with those from [7] where the total gamma and neutron flux from the quiver were seen to be of roughly the same order of magnitude as the PWR quiver. The flux values for both gammas and neutrons were roughly of the same order, taking into account the number of fuel rods in the BWR quiver when compared to the PWR quiver from [7] which holds more than twice as many rods.…”
Section: Jinst 15 P12023supporting
confidence: 83%
See 4 more Smart Citations
“…The serpentTools [28] package was used to read in the detector tallies in the output files from the particle transport calculations carried out in Serpent2 to create the plots shown in figure 8. The results from the first part of this study were found to be in line with those from [7] where the total gamma and neutron flux from the quiver were seen to be of roughly the same order of magnitude as the PWR quiver. The flux values for both gammas and neutrons were roughly of the same order, taking into account the number of fuel rods in the BWR quiver when compared to the PWR quiver from [7] which holds more than twice as many rods.…”
Section: Jinst 15 P12023supporting
confidence: 83%
“…The results from the first part of this study were found to be in line with those from [7] where the total gamma and neutron flux from the quiver were seen to be of roughly the same order of magnitude as the PWR quiver. The flux values for both gammas and neutrons were roughly of the same order, taking into account the number of fuel rods in the BWR quiver when compared to the PWR quiver from [7] which holds more than twice as many rods. Moreover, it was observed that the drop in gamma and neutron flux across the quiver lid was also comparable, where the gamma flux was reduced by a factor of 10 6 and the neutron flux dropped to zero in both PWR and BWR quivers.…”
Section: Jinst 15 P12023supporting
confidence: 83%
See 3 more Smart Citations